EFEKTIFITAS BELAJAR ANAK SEKOLAH DASAR DENGAN BIMBINGAN ORANG TUA SELAMA PANDEMI COVID-19 - Bayu Purbha Sakti; Gunawan Budi; Farida Farida (Program Studi PGSD Universitas Flores, 2022)
Children's attitudes and parental guidance in dealing with online learning during this pandemic will determine the success of learning activities in elementary schools. This type of research is a qualitative research. This research is a qualitative research. The approach used leads to the phenomenon of online learning activities. Three students and 3 parents of class III SDN 3 Ketandan Klaten were used as research subjects. Observations were made to determine the process of online learning activities. Interviews were conducted to determine parental guidance and attitudes of elementary school children who undergo online learning activities. Documentation was conducted to determine the learning outcomes experienced by elementary school children. The data analysis technique used is data reduction, presentation, and verification. The results of the study were written related to the events experienced by parents and students. Learning activities for elementary school children who receive parental guidance during the Covid-19 pandemic are influenced by several things. Things that affect the effectiveness of the learning mentioned above include the ability of parents in information technology, cellphones and whatsapp used in learning, the quality of internet signals provided by telecommunication services, the ability of children to understand learning materials and the involvement of parents accompanying children.